Aluminum-target-assisted femtosecond-laser-filament-induced water condensation and snow formation in a cloud chamber. Issue 1 (December 2018) - Liu, Yonghong; Liu, Jiansheng; Sun, Haiyi; Ju, Jingjing; Hu, Xinkai; Wang, Cheng; Leng, Yuxin
Abstract We compare the water condensation and snow formation induced by a femtosecond laser filament with that when the filament is assisted by an aluminum target located at different positions along the filament. We reveal that the laser-filament-induced water condensation and snow formation assisted by the aluminum target are more efficient compared with those obtained without the assistance of the aluminum target. We find that the mass of the snow induced by the laser filament is the largest when the aluminum target is located at the end of the filament, smaller when it is at the middle of the filament, and the smallest at the beginning of the filament. These findings indicate that a higher plasma density and the generation of vortex pairs below the filament are important for enhancing the efficiency and yield of the laser-induced water condensation and precipitation. The higher plasma density provides more cloud condensation nuclei and facilitates the water condensation; vortex pairs below the filament are favourable to the growth of particles up to larger sizes.